(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
This paper deals with the performance analysis of a point pivoted absorber, called PIVOT, developed by Seapower scarl and previously tested at the University of Naples “Federico II”. The system configuration comprises a floating body connected to a fixed frame and a Power Take Off (PTO) system. This type of wave energy converter (WEC) is categorised between a pure point absorber and a terminator. A 2D analysis was performed using a numerical model based on the Lagrangian Smoothed Particle Hydrodynamics (SPH). The open-source DualSPHysics model was used to analyse the motion of the point pivoted absorber and its ability to extract energy from the wave motion. The modelling of the mechanism of the point pivoted absorber with a PTO shaft was performed by coupling the DualSPHysics solver with the multiphysics library Chrono Project. This library implements the Discrete Element Method (DEM) for simulating multibody dynamics including collision detection and various mechanical constraints for solving complex mechanisms. The real PTO of the PIVOT WEC was a ball screw actuator with a Permanent Magnet Generator (PMG) characterised by a specific linear damping coefficient K. In this work, the PTO was simulated with a hinge through a specified value of the damping coefficient K’ around the hinge axis (i.e. a torsional damping coefficient). Therefore, the power absorbed by the floating device was calculated as a function of the torsional damping coefficient and the wave frequency of the WEC. In order to simulate the interaction between the water waves and the point pivoted absorber, a numerical wave flume was constructed. This channel was characterised by a piston-type paddle for wave generation and a final attenuation zone to dissipate the incident wave energy downstream of the device. With the aim of generating a sufficient number of incident waves along the flume, an active absorption system was implemented. In order to verify the feasibility of the results obtained by SPH simulations with regular waves, a comparison of the average absorbed power of the WEC with a potential flow solver was performed. For all simulated cases, it has been demonstrated that the energy balance is satisfied except for small negligible dissipation processes in the interaction between the waves and the WEC (i.e. the average energy flux generated by the wave maker is almost equal to the sum of the average energy flux absorbed by the WEC and that transmitted behind it). This preliminary study is the first step towards the validation of a numerical code for predicting the performance of PIVOT WECs in real conditions. In fact, future experimental tests are planned in a reserved marine area at the Marine Energy Laboratory (MEL) of the University of Reggio Calabria. To this end, irregular wave trains with energy spectra similar to those in the real world were reproduced in order to tune the device to actual sea conditions. Additional analyses with SPH focused on the evaluation of the capture width ratio (CWR) as well as the wave forces and moments acting on the device.